ECOBRICK SEBAGAI MEDIA PEMBELAJARAN PENGOLAHAN SAMPAH PLASTIK PADA SISWA SEKOLAH DASAR DI SD N 3 JARAKAN, DUSUN JARANAN, PANGGUNGHARJO, SEWON, BANTUL, DI YOGYAKARTA - Sekar Lintang Sejati; Feti Fatiah Nada Milenia; Ratih Rahmadani; Prisela Elta Kelana; Namira Salsabila Tyadin; Choirul Amri; Abdul Hadi Kadarusno (JPS : Jurnal Pengabdian Serulingmas, 2022)
Waste is a national problem so that its processing needs to be carried out in a comprehensive and integrated manner from upstream to downstream in order to provide economic, health and safety benefits for the environment. Based on this, the background for this activity is because the problem of waste is still a challenge in Bantul Regency, which is caused by the amount of volume that continues to increase every year. Lack of knowledge in processing and utilizing plastic waste is one of the factors of the existing problems. This activity was carried out using several methods, namely counseling, question and answer, and the practice of making ecobricks which were arranged into a chair. The form of waste processing and utilization that can be done is the use of ecobrick . The purpose of this activity is to instill knowledge and behavior in waste management and as a learning medium for children's creativity. The extension method aims to provide understanding and knowledge to 4th grade students at SD Negeri 3 Jarakan. One of the uses of inorganic waste into ecobricks at SD Negeri 3 Jarakan, Jaranan Hamlet, Panggungharjo Village, Sewon District , Bantul Regency, DI Yogyakarta with the target of grade 4 students. Before making ecobricks was preceded by counseling on STBM, 3R and materials on how to make ecobricks. Materials for making ecobricks were started by giving new knowledge to elementary school siblings about how to process waste that was initially considered goods. useless into something that has value. The enthusiasm of the 4th graders was reflected in their efforts when they were asked to bring inorganic waste such as plastic as materials for making ecobricks. Through making ecobricks, its hoped that elementary school students can participate in implementing the waste management program and also wisely use plastic later.